2021
DOI: 10.3390/s21041105
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Keratin with Diffuse Reflectance and Autofluorescence Imaging and Nonlinear Optical Microscopy in a Rare Keratinopathic Ichthyosis

Abstract: Keratins are one of the main fluorophores of the skin. Keratinization disorders can lead to alterations in the optical properties of the skin. We set out to investigate a rare form of keratinopathic ichthyosis caused by KRT1 mutation with two different optical imaging methods. We used a newly developed light emitting diode (LED) based device to analyze autofluorescence signal at 405 nm excitation and diffuse reflectance at 526 nm in vivo. Mean autofluorescence intensity of the hyperkeratotic palmar skin was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…An LED-based MSI device was recently successfully introduced for the detection of recurring skin cancers [43,44] and proved to be applicable in the differentiation of different tumor types from benign lesions based on their mean intensity of autofluorescence (AF) [45]. In addition, MSI has been also utilized for the detection of rare skin disorders [46,47].…”
Section: Figurementioning
confidence: 99%
“…An LED-based MSI device was recently successfully introduced for the detection of recurring skin cancers [43,44] and proved to be applicable in the differentiation of different tumor types from benign lesions based on their mean intensity of autofluorescence (AF) [45]. In addition, MSI has been also utilized for the detection of rare skin disorders [46,47].…”
Section: Figurementioning
confidence: 99%
“…Our research group has previously shown this technique to differentiate seborrheic keratosis from melanoma [ 33 ]. In addition, we introduced MSI for the diagnostics of rare skin disorders, including pseudoxanthoma elasticum [ 34 ] and keratinopathic ichthyosis [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neben der Dermatoskopie wurden weitere neuartige bildgebende Verfahren wie die nichtlineare optische Mikroskopie und die multispektrale Bildgebung als neuartige quantitative Instrumente zur Bewertung von PXE-befallener Haut eingesetzt [ 10 , 15 , 21 ]. Diese Techniken können auch für die Beurteilung einer breiteren Palette von Erbkrankheiten eingesetzt werden, darunter das Ehlers-Danlos-Syndrom, keratinopathische Ichthyose und das Marfan-Syndrom [ 2 , 6 , 16 , 20 ]. Die multimodale Bildgebung mit der Kombination von Dermatoskopie und verschiedenen bildgebenden Verfahren könnte ein weiterer Ansatz für die gründliche Untersuchung der Haut von PatientInnen mit Genodermatosen sein, der in der Diagnostik und Therapieüberwachung dieser Erkrankungen eingesetzt werden kann.…”
Section: Diskussionunclassified